Biologia da mosca-minadora Liriomyza trifolii (Burgess) (Diptera : Agromyzidae), criada em meloeiro,Cucumis melo L., em diferentes temperaturas - LIMA, Marcos Aurélio Araújo (2008)
In the last years the leafminer Liriomyza trifolii (Burgess) has become a serious pest on melon crops. To develop a pest management program it is important to know some biological aspects of this insect species. Thus, the objective of this work was to study the biology of L. trifolii, to determine its thermal requirements and its fertility life table reared in melon under different temperatures. The temperatures studied were 20, 22, 25, 28, 30 e 33ºC. Egg hatching occurred within 2.8 (30ºC) to 6.6 (20ºC) days. Larval period ranged from 2.4 to 5.9 days, at 33 and 20ºC, respectively. A variation of 7.8 (33ºC) to 19.7 (20ºC) and 13.1 (33ºC) to 32.2 (20ºC),respectively, was observed for pupal stage and from egg to adult emergence. Larvae viability was always higher than 79%, while pupae viability was always lower than 83%, reaching 35% at 20ºC. The lower threshold temperature for eggs, larvae, pupae and egg-adult periods was 12.46,13.04, 13.20 and 12.95ºC, respectively. Thermal requirement (K) for egg, larva, pupa and from egg laying to adult emergence was 47.98, 41.54, 120.19 and 211.86 degree-days. Based on thermal requirements determined for L. trifolii and average temperatures for Mossoró, Apodi and Jaguaruana were estimated that it’s able to complete up to 23 generations per year in these areas. The mean duration of one generation (T) was 23.68 and 18.15 days, respectively, at thetemperatures of 25 and 28ºC. The net reproductive rate (Ro) was higher at 25ºC, corresponding to an increase of 86.20 times at each generation. The intrinsic rate of population increase (rm) was 0.18 (25ºC) and 0.15 (28ºC) and the finite ratio of population increase ( ) was 1.21(25ºC) and 1.17 (28ºC). The best performance of L. trifolii was at 25ºC.